Pengaruh Penyuluhan Terhadap Tingkat Pengetahuan Anemia pada Ibu Hamil di Desa Pulau Panggung Kecamatan Semende Darat Laut Kabupaten Muara Enim Tahun 2023 - Nita Rukmana; Fera Meliyanti; Elwan Candra (Jurnal Ilmiah Kedokteran dan Kesehatan, 2024)
Pregnant women are still often faced with various health problems, one of which is anemia. Anemia is the biggest public health problem in the world, especially for pregnant women because many suffer from iron deficiency. WHO in 2021 reports that globally the prevalence of anemia in pregnant women worldwide is 41.8%. It is known that the prevalence of anemia in pregnant women is estimated at 48.2% in Asia, 57.1% in Africa, 24.1% in America, and 25.1% in Europe. The PulauPanggung Community Health Center supervises 10 villages where 12 people (26,66%) of the 45 pregnant women examined were Desa PulauPanggung who had the most cases of anemia. The research design used in this study was a pre-experimental type one group pretest-posttest design. The population in this study were all pregnant women in Desa PulauPanggung, Working Area of ​​the PulauPanggung Health Center, Semende Darat Laut District, Muara Enim Regency, totaling 27 people. The sample in this study were pregnant women who attended counseling at the posyandu in the Working Area of ​​PulauPanggung, Semende Darat Laut, Muara Enim Regency. Based on univariate analysis, it is known that the average value of respondents' knowledge before counseling was 58.65 out of 20 respondents. The highest value is 72 and the lowest is 50. The value that is most often obtained is 60. The average value of respondents' knowledge after counseling is 92.95 from 20 respondents. The highest score is 100 and the lowest is 82. The highest score is 98. From 20 respondents, the average value of mothers' knowledge before counseling (pre-test) was 58.65. From 20 respondents, the average value of mothers' knowledge after counseling (post-test) was 92.96. There is an effect of health counseling on the level of mother's knowledge about anemia before and after counseling with the lecture method and audio-visual media in PulauPanggung Village, Semende Darat Laut District, Muara Enim Regency in 2023 with a p value of 0.000.